Implementation Dhampster Shafer Method to Diagnose Infected Patients Mers Cov Virus - Alwin Fau; Mailani Safittri; Anisa Puji Arni (STMIK Budi Darma, 2021)
Mers Cov virus or often referred to as Covid-19 is a very language virus that can damage the respiratory system in humans. This virus works very quickly and is able to develop and reproduce itself in the human body if the handling process is not fast. Various symptoms that can be caused by this virus attack are causing symptoms of fever, flu and shortness of breath so that it can cause people who have been infected with the virus to die. An expert system is a field of science in which a person's knowledge or expert will be stored in the system to make it easier to consult on the symptoms caused by the Mers Cov virus. The Dempster Shafer method is a method that works in the representation, combination or combination and distribution of uncertainty, where this theory has an institute nature according to the thinking pattern of an expert based on strong mathematics. This expert system is able to produce the same information as the decision of an expert who is able to diagnose someone whether the virus is infected with Mers Cov or not. With this expert system, it will make it easier to conduct consultations related to the symptoms of the mers cov virus virus The success rate of the Dhampster Shafer Method in diagnosing patients infected with Mers Cov Virus has a percentage of 0.8 or 8%.